2013
DOI: 10.1186/1532-429x-15-97
|View full text |Cite
|
Sign up to set email alerts
|

Steady state vascular imaging with extracellular gadobutrol: evaluation of the additional diagnostic benefit in patients who have undergone a peripheral magnetic resonance angiography protocol

Abstract: BackgroundTo evaluate the feasibility and additional diagnostic benefit of a high-resolution steady state 3D-volume interpolated breath-hold exam (VIBE) sequence between a continuous table movement (CTM) MR angiography of the entire runoff vasculature and a time-resolved (TWIST) MRA of the calves.MethodsIn this retrospective IRB approved study 224 patients (72 women, 152 men, mean age 67.29 ± 13.9) were included who had undergone a low-dose MR angiographic protocol at 3T (Siemens TimTrio) after injection of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Compared with 0.5 M of other gadolinium‐containing contrast agents, the bolus injection of gadobutrol resulted in peak concentration in a shorter time. Previous studies have shown that gadobutrol showed significant advantages in MR angiography and perfusion imaging …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with 0.5 M of other gadolinium‐containing contrast agents, the bolus injection of gadobutrol resulted in peak concentration in a shorter time. Previous studies have shown that gadobutrol showed significant advantages in MR angiography and perfusion imaging …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that gadobutrol showed significant advantages in MR angiography and perfusion imaging. 18,19 In the present study the standard dose (equimolar dose) of gadobutrol and Gd-DTPA was used in the enhanced MR scan of brain metastases. The enhancement in brain metastases was significantly higher when using gadobutrol compared with Gd-DTPA at 3, 7, and 10 minutes postenhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Beside its key role in research, CMR is most frequently used clinically for the carotid arteries where it can be used to characterize thrombus, [ 41 ] plaque components, [ 42 ] plaque vulnerability, atheroma burden, natural history of progression, and response to treatment. However, peripheral artery angiography, [ 43 45 ] and the role in investigation of pulmonary hypertension, [ 46 ] vasculitis and systemic hypertension, [ 47 ] is also making progress. This is an area of CMR where contrast agents, [ 48 ] and 3 T has had an impact [ 49 , 50 ].…”
Section: Atheroma Vascular Aorta Valvesmentioning
confidence: 99%
“…This paper details the additional diagnostic benefits that can be achieved with imaging during the blood-pool phase following injection of an extracellular contrast agent for peripheral contrast-enhanced angiography [ 13 ]. Although the study is retrospective, the analysis, discussion and references list are comprehensive.…”
Section: Vessel Wall and Mr Angiographymentioning
confidence: 99%